Flightless birds - Barrett, Norman S. (New York : F. Watts, 1991)
Examines the physical features, nesting, and feeding habits of several flightless birds, including the ostrich, rhea, emu, and cassowary.
Includes index.
3-5.
6.1
3-6
Keywords: Flightless birds -- Juvenile literature; Birds; Flightless birds; Birds; Flightless birds